EPISTEMOLOGY OF THE ENVIRONMENT FOR BIODIVERSITY CONSERVATION: VALIDATION OF A DIAGNOSTIC INSTRUMENT - Reinaldo, Thais Adrianne Silva [UNESP]; Vicente, Luene Pessoa; Silveira, Anais Freitas; Ayres, Ariadne Dall'aqua; Brando, Fernanda da Rocha; Caldeira, Ana Maria de Andrade [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2024)
The relationship between climate and biodiversity is complex and requires research that, through environmental, social and economic crises, guide decision-making for the conservation of biodiversity that is environmentally and socially appropriate and viable. In this sense, it is imperative to point out ways, mainly through Environmental Education, adapted to the conceptions and values about biodiversity protection found in society, in order to provide responses as fast and efficient as the environmental crises demand. Therefore, this article aimed to present the validation and potential of a diagnostic instrument that helps to understand this range of values and ideas. The instrument, built based on Likert scaling, was semantically and statistically validated and resulted in three potential axes of analysis: anthropic, biological and geosystemic. These axes can be analyzed according to the context of application, articulate issues involved in the complexity of environmental factors and guide decision-making in the environmental area.
Keywords: Environmental education; Environmental conception; Quantitative analysis; Basic education